Medical students’ perceptions on preparedness and care delivery for patients with autism or intellectual disability - Bitektine, E; Hintermayer, MA; Chen, A; Ko, A; Rodriguez, C (Canadian Medical Education Journal, 2024)
Introduction: To provide competent care to patients with autism spectrum disorder (ASD) or intellectual developmental disorder (IDD), healthcare professionals must recognize the needs of neurodivergent populations and adapt their clinical approach. We assessed the perceived preparedness of medical students to adapt care delivery for patients with ASD/IDD, as well as their perceptions on neurodiversity education. Methods: We conducted a sequential explanatory mixed-methods study on undergraduate medical students at McGill University during the academic year 2020-2021. We administered an online survey, followed by semi-structured interviews. We analyzed data using descriptive statistics and thematic analysis. We integrated findings at the interpretation level. Results: We included two-hundred-ten survey responses ( 29% of class), and 12 interviews. Few students felt prepared to adjust care for patients with ASD/IDD despite most indicating doing so was important. Ninety-seven percent desired more training regarding care accommodation for neurodivergent patients. Thematic analysis unveiled the perception of current insufficient education, and the value of experiential learning. Discussion/Conclusions: This study highlights low perceived preparedness of medical students to accommodate care for neurodivergent patients, and a desire for more instruction. Incorporating interactive training in medical school curricula regarding modifying care delivery for neurodivergent individuals may improve the perceived preparedness of medical trainees to work with these patients and care quality.